A molecular framework for lc controlled locule development of the floral meristem in tomato - Xiang, Hengzuo; Meng, Sida; Ye, Yunzhu; Han, Leilei; He, Yi; Cui, Yiqing; Tan, Changhua; Ma, Jian; Qi, Mingfang; Li, Tianlai (Frontiers in Plant Science, 2023)
Tomato malformed fruit with multiple locules is a common physiological disorder that significantly affects the quality of tomatoes. Research has shown that the occurrence of malformed fruit in tomatoes is closely linked to the number of locules, and two key QTLs, lc and fas, are involved in controlling this trait. It has been observed that lc has a relatively weaker effect on increasing locule number, which is associated with two SNPs in the CArG repressor element downstream of the SlWUS. However, the precise molecular mechanism underlying lc is not yet fully understood. In this study, we investigated the role of lc in tomato locule development. We found that the number of floral organs and fruit locules significantly increased in tomato lc knockout mutants. Additionally, these mutants showed higher expression levels of the SlWUS during carpel formation. Through cDNA library construction and yeast one-hybrid screening, we identified a MADS-box transcription factor SlSEP3, which was found to bind to lc. Furthermore, we observed an increase in floral organs and fruit locules similar with lcCR plant on SlSEP3 silencing plants. However, it should be noted that the lc site is located after 3’ untranslated region (UTR) of SlWUS in tomato genome. As a result, SlSEP3 may not be able to exert regulatory functions on the promoter of gene like other transcription factors. In the yeast two-hybrid assay, we found that several histone deacetylase (SlHDA1, SlHDA3, SlHDA4, SlHDA5, SlHDA6, SlHDA7, and SlHDA8) can interact with SlSEP3. This indiacted that SlSEP3 can recruit these proteins to repress nucleosome relaxation, thereby inhibiting SlWUS transcription and affecting the locule number of tomato fruit. Therefore, our findings reveal a new mechnism for lc playing a significant role in genetic pathway regulating tomato locule development.